Geomagnetically induced currents in the Irish power network during geomagnetic storms. Issue 12 (15th December 2016) - Blake, Seán P.; Gallagher, Peter T.; McCauley, Joe; Jones, Alan G.; Hogg, Colin; Campanyà, Joan; Beggan, Ciarán D.; Thomson, Alan W. P.; Kelly, Gemma S.; Bell, David
Abstract: Geomagnetically induced currents (GICs) are a well‐known terrestrial space weather hazard. They occur in power transmission networks and are known to have adverse effects in both high‐latitude and midlatitude countries. Here we study GICs in the Irish power transmission network (geomagnetic latitude 54.7–58.5°N) during five geomagnetic storms (6–7 March 2016, 20–21 December 2015, 17–18 March 2015, 29–31 October 2003, and 13–14 March 1989). We simulate electric fields using a plane wave method together with two ground resistivity models, one of which is derived from magnetotelluric measurements (magnetotelluric (MT) model). We then calculate GICs in the 220, 275, and 400 kV transmission network. During the largest of the storm periods studied, the peak electric field was calculated to be as large as 3.8 V km −1, with associated GICs of up to 23 A using our MT model. Using our homogenous resistivity model, those peak values were 1.46 V km −1 and 25.8 A. We find that three 400 and 275 kV substations are the most likely locations for the Irish transformers to experience large GICs. Key Points: Surface electric fields and geomagnetically induced currents (GIC) were simulated in the Irish power network for five geomagnetic events A multilayered resistivity model to a depth of 200 km was made using magnetotelluric measurements for use in GIC simulations in Ireland GICs have been replicated for Kp6 and Kp7 storms, and predicted for Kp9 storms in Ireland